The last of the mohicans eaudiobook - Cooper, James Fenimore (Leatherstocking Tales, 1989)
Cooper was one of the first writers to treat America's westward expansion as a great and ongoing epic; it was a theme of conflict-between civilization and the untouched wild, white culture and its insistent encroachments on the cultures of native America. Cooper fills his novels with legend and folklore, tall-tales, romance, and an earthy individualism. This American frontier classic chronicles the adventures of Hawkeye and his Indian friend, Chingachgook, during the French and Indian War.